А.ДАБЫЛОВТЫҢ «БАҲАДЫР» ДӘСТАНЫНДА ФОЛЬКЛОРЛЫҚ МОТИВЛЕР - Алланазаров, Е. (FAN va JAMIYAT, 2020)
In the article is devoted to the using of traditional customs of folklore epic dastans, by the folk poet A.Dabilov showing realistic new verge of traditional customs in creating the dastan “Bahadir”. It is also analysed that the given work evokes in readers the feelings, connected with the image of real life and with people’s friendship.